Preparation and Implementation of Government Regulations in Lieu of Laws as a Government Tool to Handle the Economic Crisis in Indonesia - Parikesit, Satya Bhakti; Redi, Ahmad (Greenation Publisher & Yayasan Global Resarch National, 2025)
The preparation and implementation of Government Regulation instead of Law (PERPU) is one of the main strategies used by the Indonesian government to deal with the ongoing economic crisis. In the context of global economic uncertainty and the impacts felt domestically, PERPU is flexible for the government to quickly respond to emergencies without waiting for a long legislative process. This article aims to analyze the role of PERPU in responding to various economic challenges, from business sector recovery to increasing socio-economic stability. In addition, this study also assesses the effectiveness of the implementation of PERPU in overcoming structural problems arising from the crisis and its impact on long-term economic policy in Indonesia. By using a policy analysis approach, it is desired to obtain a deeper understanding concerning the contribution of PERPU in reducing the crisis and accelerating Indonesia's economic recovery.